Jewish culture as a vital element of local identity trought history – mini project carried on Faculty of Education in Sombor - Štrangarić, Snežana; Beljanski, Mila; Matin, Ines (Norma, 2022)
In this paper we presented the activities that we conducted within the mini project named Jewish culture as a vital element of local identity trough history, as well as the idea and the goals that stand behind the project. The project was conducted on Faculty of Education in Sombor. The main goal of this project was for students-future teachers, to acquire knowledge about the Jewish culture, religion and history, so they could develop skills for better understanding the specific local identity as part of Vojvodina, which is a unique multi-cultural and multi-confessional region, and also to improve their intercultural competences. The possibilities and methods for teaching and learning about the Holocaust are also examined. The project activities included lectures about the main characteristics of Jewish culture, and about local history and suffering of Jewish families from Sombor during the Holocaust. The plan included a visit to Jewish community in Sombor, and also a trip to Subotica, the city in the same region, in order to visit a restored synagogue.
Keywords: Jews; culture; interculturalism; Holocaust; synagogue